The Brazilian cohort of pulp and paper workers: the logistic of a cancer mortality study - Fassa Anaclaudia Gastal; Facchini Luiz Augusto; Dall'Agnol Marinel Mór (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 1998)
The International Agency for Research on Cancer (IARC) proposed this international historical cohort study trying to solve the controversy about the increased risk of cancer in the workers of the Pulp and Paper Industry. One of the most important aspects presented by this study in Brazil was the strategies used to overcome the methodological challenges, such as: data access, data accuracy, data availability, multiple data sources, and the large follow-up period. Through multiple strategies it was possible to build a Brazilian cohort of 3,622 workers, to follow them with a 93 percent success rate and to identify in 99 percent of the cases the cause of death. This paper, has evaluated the data access, data accuracy and the effectiveness of the strategies used and the different sources of data.